PENDIDIKAN KARAKTER BERBASIS KONSEP SPIRITUAL TEACHING DALAM PEMBELAJARAN ONLINE DIMASA PANDEMI - Salma Maulida; Khamim Zarkasih Putro; Shomiyatun (QURROTI, 2021)
Online learning during the pandemic has created confusion for educators and parents alike. The lack of socialization and interaction of children with teachers indirectly makes children less able to control their attitudes so that good characters are not built optimally. In this study, the researcher will examine the character building efforts carried out by RAM NU 075 Joresan Mlarak Ponorogo in online learning based on the concept of spiritual teaching. This concept is considered quite effective in responding to and following the development of children's attitudes and logic. In this study, the researcher used the type of case study research. Case study research is said to be a method of inquiry that is carried out directly, with a natural background and its attention is focused on an event intensively and in detail. The research method is a qualitative research method, which is a research approach that is oriented to events or natural phenomena. With character education based on the concept of Spiritual Teaching which was applied at RA Muslimat NU 075 Joresan, it was found that this method was quite effective in shaping the character of children. In online learning like today, children rarely meet and greet teachers and their friends, so that children's social-emotional development does not develop optimally. So that children have less control to control their attitude when they meet. With the habit of rote memorization and religious-based assignments, children's attitudes and character begin to form well. Children begin to have boundaries to control their attitudes and behavior in everyday life and interact with others.